Determinanty rozwoju kanałów dystrybucji produktów żywnościowych - Nasalski, Zbigniew (Determinants of Development of Distribution Channels of Food Products, 2005)
Increase of competition on food market after the integration with EU and mutual economic codependence of agriculture, food industry and distribution influences acceleration of modernization process of food distribution channels products. Selected factors determining the development of distribution channels present an important part of a wide process, which should be realised with consideration, detailed individual specificity of food markets (products). Full adaptation to structures of European markets requires support, among others concentration and integration process with different agribusiness links participation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 113-118